Implantable defibrillator-computed respiratory disturbance index predicts new-onset atrial fibrillation: the DASAP-HF study. (14th October 2021) - Boriani, G; Pisano', E.C.L; Pieragnoli, P; Locatelli, A; Capucci, A; Talarico, A; Zecchin, M; Rapacciuolo, A; Piacenti, M; Indolfi, C; Arias, M.A; Diemberger, I; et al.
Abstract: Introduction: Sleep apnea (SA), as measured by polysomnography, is a risk factor for atrial fibrillation (AF). The DASAP-HF study previously demonstrated that the Respiratory Disturbance Index (RDI) computed by an implantable cardioverter defibrillator (ICD) algorithm accurately identifies severe SA, is associated with cardiovascular events, and independently predicts death. Purpose: In the present analysis we tested the hypothesis that device-detected RDI could also predict AF burden. Methods: Patients with left ventricular ejection fraction ≤35% implanted with an ICD were enrolled and followed-up for 24 months. One month after implantation, patients underwent a polysomnographic study. The weekly average RDI value was considered, as calculated by the algorithm during the entire follow-up period and over a 1 week period preceding the sleep study, and patients were stratified according to an RDI value ≥ or <30 episodes/hour. The endpoints were: daily AF burden of ≥5 minutes, ≥6 hours, ≥23 hours. Results: 164 enrolled patients had usable RDI values during the entire follow-up period. Severe SA (RDI≥30 episodes/h) was diagnosed in 92 (56%) patients at the time of the polysomnographic study. During a median follow-up of 25 months, AF burden ≥5 minutes/day was documented in 70 (43%), ≥6 hours/day in 48 (29%), and ≥23 hours/day in 33 (20%) patients. Device-detected RDI≥30 episodes/h at the time of the polysomnographic study, as well as the polysomnography-measured apnea hypopnea index ≥30 episodes/h, were not associated with the occurrence of the endpoints, using a Cox regression model. However, using time-dependent Cox model continuously measured weekly average RDI≥30episodes/h was independently associated with AF burden ≥5 minutes/day (HR: 2.13, 95% CI: 1.24–3.65, p=0.006), ≥6 hours/day (HR: 2.75, 95% CI: 1.37–5.49, p=0.004), and ≥23 hours/day (HR: 2.26, 95% CI: 1.05–4.86, p=0.037), after correction for history of AF, left atrial diameter, and gender. Conclusions: In heart failure patients implanted with an ICD, device-diagnosed severe SA is associated with a higher risk of AF. In particular, severe SA on follow-up data review identifies patients who are from two- to three-fold more likely to experience an AF episode, according to various thresholds of daily AF burden. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Promoted by the Italian Heart Rhythm Society (AIAC).Supported by a research grant from Boston Scientific.